MULTIPLE CHOICE QUESTIONS (MCQS) VS SHORT ANSWER QUESTIONS (SAQS) FOR INFERENTIAL COMPREHENSION - Budiyono, B (Universitas Nusantara PGRI Kediri, 2018)
Among a variety of item types or test formats, multiple-choice tests are much more associated with many advantages. However, short-answer questions as a type of open-ended questions are proposed to be more appropriate for measuring inferential skills. This study investigated this particular issue to provide evidence whether it was the case in college reading for inferences of implied main ideas. The findings indicate that the performance in MCQs was significantly much better than that in SAQs. A recommendation would be a blend of MCQs and SAQs in measurement of inferential comprehension of main ideas with greater weighting on SAQs. Keywords: multiple-choice, short-answer, inference, significant